Stories - Julian Preece (Transnational Modern Languages. A Handbook)
This chapter argues that classic tales in the western tradition are transnational in origin, including many found in the Bible, Homer and canonical compilations which became foundational texts of national literatures, such as The Decameron, The Canterbury Tales, Don Quixote or epic poems telling the deeds of Arthurian heroes. For good and ill, narrative fictions, in the form of legends and fables, but also jokes, rumours and 'fake news', jump across languages and traverse physical and man-made boundaries. Walter Benjamin may distinguish between the story-teller who stays at home and learns the stories of their place of origin and the traveller who brings back accounts of their journeys, but the stories passed on by both archetypes have come from afar.